Psychoanalysis and juvenile justice: The psychoanalytic function within the juvenile court - Di Toppa, Umberto (Quaderni di Psicologia Clinica, 2022)
This paper aims to contribute to the reflection on clinical psychological intervention with a psychoanalytic orientation capable of intervening within the most different contexts, while maintaining its specificity. The goal of this contribution is to develop a thought on the psychoanalytic function within the juvenile court and in particular with respect to the role of the juvenile honorary judge. Through an exploration of the context of the juvenile court and the role of the juvenile honorary judge, we intend to build a hypothesis on the possibility, in a context crossed by an individualistic, prescriptive and factual culture, to reintegrate elements of subjectivity, relationship and context; the goal is to deal with the competence of families to manage the events of coexistence and to contain violence, which risks becoming exasperated within the culture of prescriptions.